Suppression head impulse test in children—experiences in a tertiary paediatric vestibular centre - Dasgupta, Soumit; Crunkhorn, Rosa; Wong, John; McMahon, Annie; Ratnayake, Sudhira; Manzari, Leonardo (Frontiers in Neurology, 2024)
The suppression head impulse paradigm (SHIMP) involves suppression of the vestibulo-ocular reflex (VOR) and anticompensatory saccades generated thereof. SHIMP is gaining importance to understand vestibular compensation with its different parameters (VOR gain/peak saccadic velocity PSV/latency of saccades). SHIMP studies are emerging in adults, but pediatric studies have hardly been performed. This study is a retrospective case note audit over a period of 2 months in a tertiary pediatric vestibular center in the United Kingdom to investigate whether SHIMP is safe/robust to be used in children conforming to existing standards/norms in normal children and whether it yields any meaningful inferences in pediatric vestibular hypofunction. This is the largest pediatric SHIMP study to date. A total of 44 referred children (6–18 years, female children>male children) with a range of complaints from dizziness, imbalance, motor incoordination, postural instability, and hearing loss were included, and their SHIMP parameters were measured. All children underwent comprehensive functional/objective audiovestibular assessments. Two groups were defined—Group A with normal vestibular function and Group B with abnormal vestibular function. The normal population showed an average SHIMP VOR gain of 0.98+/−0.08 and latency of overt saccades at 215.68+/–46.16 milliseconds agreeing with published evidence. The PSV of overt saccades was 315.39+/−56.30/s, and there was a gain asymmetry of 7.42+/−4.68 between the sides. Statistically significant differences with moderate/large effect sizes were observed between the groups in terms of VOR gain and PSV but not in saccade latencies. Covert saccades were rare in SHIMP, while overt saccades were observed in 100% of children. VOR gain difference between the head impulse paradigm (HIMP) and the SHIMP was significant as well. We observed statistically significant differences in side asymmetry of VOR gain between the groups. Furthermore, we identified a group of children with cerebellar lesions where overt saccades in SHIMP were rather low in number. Further research is recommended to investigate pediatric PSV, asymmetry, and inability to generate overt saccades that may suggest useful means to assess compensation and central function. We conclude that SHIMP yields valuable information and is a safe, easy to perform, and a reliable test that should be used in children to supplement HIMP.